Efisiensi Bahan Bakar Armada Alat Konstruksi melalui Eco-Driving dan Rantai Pasok - Didit Darmawan; Mahesa Dzulsyafiqri Muid; Fatih Arsyad Dharmawan; Fayola Issalillah; Rahayu Mardikaningsih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Construction machinery fleets consume substantial diesel fuel and produce significant emissions. Two approaches fuel efficiency through driver behavior change and alternative fuel supply chain management are examined separately. This qualitative literature study explores how eco-driving techniques and alternative fuel logistics can work together to reduce fuel consumption on construction projects. Eco-driving tailored to earthmoving equipment yields savings between five to fifteen percent. Biodiesel blends above B40 require engine modifications but reduce carbon emissions. Compressed natural gas offers stable fuel pricing but demands high pressure storage infrastructure. Supply chain optimization including demand forecasting, real time inventory monitoring, and scheduled deliveries prevents fuel shortages. Integration of driving data with logistics planning creates synergy that outperforms standalone applications. Management commitment and operator incentives are critical success factors.